2004
DOI: 10.1161/01.cir.0000141734.43393.be
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Human Ventricular Repolarization by Noncontact Mapping

Abstract: Background-Noncontact mapping (NCM) has not been validated as a clinical technique to measure ventricular repolarization. We used NCM to determine repolarization characteristics by analysis of reconstructed unipolar electrograms (UEs) at the same sites as monophasic action potential (MAP) recordings in the human ventricle. Methods and Results-MAPs were recorded from a total of 355 beats at 46 sites in the left or right ventricle of 9 patients undergoing ablation of ventricular tachycardia guided by NCM (EnSite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 30 publications
3
67
0
Order By: Relevance
“…In humans with preserved ventricular function, TRT is also dependent on activation-repolarization coupling, such that reduced coupling increases TRT dispersion when measured during steady-state pacing (7,9,24,25). We evaluated coupling by measuring the slope of the AT-ARI relationship, and a slope deviating from Ϫ1 indicated less coupling (7,26). During the basic drive in our patients, the AT-ARI slope at early sites (Ϫ0.5) deviated to the same extent from Ϫ1 as the AT-ARI slope of late sites (Ϫ1.5), thereby producing similar TRT dispersion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans with preserved ventricular function, TRT is also dependent on activation-repolarization coupling, such that reduced coupling increases TRT dispersion when measured during steady-state pacing (7,9,24,25). We evaluated coupling by measuring the slope of the AT-ARI relationship, and a slope deviating from Ϫ1 indicated less coupling (7,26). During the basic drive in our patients, the AT-ARI slope at early sites (Ϫ0.5) deviated to the same extent from Ϫ1 as the AT-ARI slope of late sites (Ϫ1.5), thereby producing similar TRT dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…For biphasic T waves, local repolarization was computed from the midpoint between the two phases of the T wave (20,24,25). Although Coronel et al (5) have argued that the original Wyatt method more accurately measures the end of local repolarization in isolated pig hearts, in vivo human studies (4,26) have consistently shown significant underestimation with this method when the T wave is positive. In these studies, the modified Wyatt method provided better correlation with monophasic action potential duration (MAP 90) than the original Wyatt method, so the former approach continues to be implemented to define the local repolarization in humans (10).…”
Section: Study Populationmentioning
confidence: 99%
“…ARI was calculated by subtracting activation time from repolarization time. ARI has been previously validated and shown to correlate well with local action potential duration (56)(57)(58)(59). In addition, it serves as a method of recording action potential duration without causing myocardial injury.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology has been described extensively and validated previously. 18,21,22 A multielectrode basket catheter 23 was used to record 32 unipolar contact electrograms from the RV simultaneously with the noncontact mapping signals. In addition to the endocardial mapping signals from the RV and LV, wide bipole signals were recorded between the distal electrodes of the standard EP catheters each placed in the RV free wall and left atrial free wall.…”
Section: Mapping Of Vfmentioning
confidence: 99%